Report of the Committee on Distribution of Income and Levels of Living Part II Changes in Levels of Living - Planning Commission (Planning Commission, 1969)
In this part of the report we may consider what changes have taken place in the levels of living or whether there has been any reduction of disparities in the level of living over the decade under review. It is necessary, at this stage, to consider a little carefully the concept of the level of living. It is generally agreed that it is not possible to have one single measure or index of the level of living. There are many aspects of the level of living such as availability of food, clothing, housing, employment, education, care of health, social and cultural amenities etc., each of which requires to be assessed separately. The subject has received much attention in recent years.
Government of India Planning Commission
Government of India Planning Commission